OBSTACLES TO TRIPLE HELIX MODEL: A STUDY WITH PROFESSORS IN MINAS GERAIS STATE - Athayde, André Luiz Mendes; Paula, Pablo Peron de; Silva, Larissa Oliveira; Castro, Priscilla Nogueira; Couto, Felipe Fróes (Revista Brasileira de Gestão e Desenvolvimento Regional, 2022)
The present work seeks to analyze the perception of professors about the possibilities and difficulties of integration between University, Market and Government in the local context of Montes Claros-MG, Brazil. This study was carried out using mixed methods. Methodological procedures were carried out based on qualitative data collection through semi-structured interviews and quantitative data collection performed by survey questionnaires. Data was triangulated for a better analysis of the findings. Four practical issues emerged as important factors that influence the integration capacity among the agents: fragility and lack of institutional support to ensure legal stability; motivations of Professors; the need of external agents interest for the activities carried out at the university and, finally, the importance of an administrative technostructure capable of providing support.